Reflection as a Basic Category of a Teacher's Thinking and Action - Agnieszka Głowala; Maciej Kołodziejski; Tomas Butvilas (Ignatianum University Press, 2023)
Reflection in the work of a teacher is an important issue from the perspectives of linking educational theory and practice, a teacher's personal and professional development and solving educational problems in multiple contexts. The world besets the modern teacher with new challenges, and (self-)reflection becomes a necessity as well as a difficult intellectual task. This paper focusses on the issue of a teacher's reflection from the standpoint of linking educational theory and practice and examining the value of their work. Using numerous foreign and Polish publications on the subject, while also referring to classic authors such as Dewey and Schön, the authors analyse the essence of a teacher's reflection in order to highlight the significance of reflective thinking as a key competence for teachers and educators. In the deliberations in this paper, reflection is the foundation of a teacher's reflexivity in modern education, and a priority in preparing individuals for the profession. The method of a systematic and critical selected literature review was used. Special attention was paid to reflective thinking as well as the flexibility of educational processes and communicative interaction with educational entities.